2020
DOI: 10.1002/bimj.201900388
|View full text |Cite
|
Sign up to set email alerts
|

An iterative method to protect the type I error rate in bioequivalence studies under two‐stage adaptive 2×2 crossover designs

Abstract: Bioequivalence studies are the pivotal clinical trials submitted to regulatory agencies to support the marketing applications of generic drug products. Average bioequivalence (ABE) is used to determine whether the mean values for the pharmacokinetic measures determined after administration of the test and reference products are comparable. Two‐stage 2×2 crossover adaptive designs (TSDs) are becoming increasingly popular because they allow making assumptions on the clinically meaningful treatment effect and a r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…These recommendations were issued by the European Medicines Agency (EMA) and the US Food and Drug Administration (FDA) (see e.g., Muñoz et al, 2016; Davit et al, 2012, for more details). The amount of expansion is limited by the authorities, and several recent publications have shown that the TIER can be larger than the nominal level α (see e.g., Wonnemann et al, 2015; Muñoz et al, 2016; Endrenyi and Tothfalusi, 2019; Molins et al, 2021; Schütz et al, 2022, and the references therein) and therefore have proposed different ways to correct for it (see also Labes and Schütz, 2016; Tothfalusi and Endrenyi, 2016; Ocaña and Muñoz, 2019; Deng and Zhou, 2020). These corrections not only ensure that the TIER is smaller than or equal to α , but also lead to acceptance regions that change more smoothly with σ ν .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…These recommendations were issued by the European Medicines Agency (EMA) and the US Food and Drug Administration (FDA) (see e.g., Muñoz et al, 2016; Davit et al, 2012, for more details). The amount of expansion is limited by the authorities, and several recent publications have shown that the TIER can be larger than the nominal level α (see e.g., Wonnemann et al, 2015; Muñoz et al, 2016; Endrenyi and Tothfalusi, 2019; Molins et al, 2021; Schütz et al, 2022, and the references therein) and therefore have proposed different ways to correct for it (see also Labes and Schütz, 2016; Tothfalusi and Endrenyi, 2016; Ocaña and Muñoz, 2019; Deng and Zhou, 2020). These corrections not only ensure that the TIER is smaller than or equal to α , but also lead to acceptance regions that change more smoothly with σ ν .…”
Section: Introductionmentioning
confidence: 99%
“…This method involves the linear adjustment of equivalence limits based on the value of σ ν within the reference group, while still requiring that falls within the equivalence margins (– c, c ). Despite the authorities’ constraints on the degree of expansion, recent studies have revealed that the TOST can exceed the nominal level α (see, for example, Wonnemann et al, 2015; Muñoz et al, 2016; Endrenyi and Tothfalusi, 2019; Molins et al, 2021; Schütz et al, 2022, and references therein), leading to proposals for correction methods that ensure a level- α test. Moreover, these corrections also result in more seamless changes to the acceptance regions as σ ν varies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These recommendations were issued by the European Medicines Agency (EMA) and the US Food and Drug Administration (FDA) 20,30 . The amount of expansion is limited by the authorities, and several recent publications have shown that the size of the SABE can be larger than the significance level α$$ \alpha $$ 20,26,31‐33 and therefore have proposed different ways to correct for it 28,34‐36 . These corrections ensure that the size is smaller than or equal to α$$ \alpha $$ and lead to acceptance regions that change more smoothly with σν$$ {\sigma}_{\nu } $$.…”
Section: Introductionmentioning
confidence: 99%
“…Regulators also allow using two-stage adaptive designs (TSD) with unblinded interim sample size re-estimation based on the usual 2×2 crossover RT/TR design with bioequivalence limits 0.80-1.25 (in the original scale), whose application is becoming increasingly popular. This design is also useful for HVD (7,10,11,(21)(22)(23)(24)(25).…”
Section: Two-stage Adaptive Designsmentioning
confidence: 99%